Kajian Perlindungan Terhadap Perempuan dan Anak Serta Pencegahan Terhadap Bullying - Taty Fauzi; Leo Ferdian; Natasha Intania (Jurnal Lentera Pedagogi, 2024)
This research aims to find out: 1) understanding of the protection of women and children, 2) implementation of control by teachers and staff in the school environment regarding all forms of violence, 3) involvement of parents in educating children's behavior and character at home. The research method uses a qualitative approach with a case study design. Data collection through observation, literature study and documentation. The research results prove: 1) not all people understand the importance of protecting women and children, 2) the implementation of controlling children's comfort in study rooms and school environments is still not optimal, 3) parents feel their job is only at home, and teachers are the ones who are obliged to carry out further education, 4) the stigma against women and children being weak and easy to manipulate still exists. Facts in the field prove that women still often experience hidden violence characterized by harsh treatment, 5) hidden bullying on a low scale occurs in the school environment. If left unchecked, it will become a time bomb for the safety and comfort of women and children in carrying out their roles.